Varroa destructor and its impacts on honey bee biology - Morfin, Nuria; Goodwin, Paul H.; Guzman-Novoa, Ernesto (Frontiers in Bee Science, 2023)
Varroa destructor is considered one of the greatest threats to the health of the honey bee, A. mellifera. In recent years, there has been a considerable increase in the number of studies on the mite and its interaction with the bee at a cellular and molecular level. However, these studies have also revealed just how complex the interaction is. A significant factor in the virulence of V. destructor is the proteins secreted in its saliva, but only a fraction of these have yet been examined. These proteins can negatively affect the bee's immune system and promote viruses associated with mite parasitism. Initially, studies on parasitized bees concentrated on immune-related genes, but as more genes of the bees have been examined, it is clear that many other aspects of the bee are affected, such as metabolism and neural functioning. Some of those could be responsible for the detrimental changes in certain behaviors of parasitized bees, which compromises the health of the entire colony. Several viruses are associated with V. destructor parasitism, but it remains difficult to distinguish the effects of the viruses from those of the mite. Reduced immunity in parasitized bees also opens the possibility of secondary microbial infections, adding complexity to the mite-bee interaction. Further complicating studies is the impact of other factors, like agrochemicals, which can alter how V. destructor parasitism affects bee immunity, metabolism, and neural functioning. In addition, differences due to age and sex of the bee being parasitized is a factor that needs to be considered in all studies. While much has been learned in recent years about this complex interaction, the number of unanswered questions only increases.